THE PRAGMATIC THOUGHT AND ECONOMIC RATIONALITY IN LOCAL LEGISLATIVE POLICY FORMATION: AN ETHNOGRAPHIC STUDY - Asmara, Teddy; Aspin N, Ester Elisabeth; Arif, Faisal (Masalah-Masalah Hukum, 2025)
This study explores the role of economic rationality in legislative processes, particularly in the context of local regulations in Indonesia. Focusing on the Kutawangi Regional Regulation on Cultural Heritage, the research highlights how economic interests shape legislative actions, leading to inefficiencies and failures in legal protection for cultural heritage. Through ethnographic case studies, the research examines the interactions among legislators, NGOs, and other stakeholders, revealing a pattern of pragmatic economic rationality that prioritizes personal and institutional benefits over policy substance. The study finds that such practices—such as outsourcing academic text production and manipulating legislative procedures—undermine the quality and effectiveness of laws. The research further uncovers the widespread use of symbolic legislation and bureaucratic pathologies as strategies to meet performance targets without addressing substantive policy issues. The findings suggest that these practices not only compromise legislative integrity but also reflect broader systemic issues in governance. To improve legislative quality and restore public trust, the study advocates for interventions such as ethics training, anti-corruption programs, and enhanced transparency in legislative processes.